Challenges in the application of Public Procurement Act (Act 663): Case Study procurement of works in Shama District - Ofosu-Teye, Felix (2014)
A thesis submitted to the Department of Building Technology, Kwame Nkrumahy University of Science and Technology In partial fulfilment of the requirements for the award of